PENGARUH KONSENTRASI IAA TERHADAP KEBERHASILAN SAMBUNG PUCUK BEBERAPA KULTIVAR DURIAN (Durio ziberthinus Murr.) - Rahmi Sari H (LP2MTBM MAKARIOZ, 2018)
This study aims to determine the effect of IAA concentration on the success of shootssome durian cultivars. This study uses Factorial Completely Randomized Design (RAL), which consists of twofactors, namely the first factor is the concentration of IAA (I), with four levels of treatment, namely: Io = 0 ppm, h = 40 ppm, fc =80 ppm, and I3 = 120 ppm. The second factor was durian (K) cultivars with three treatment levels, namely: Ki = cultivarKalimantan, K2 = Kani cultivars, and K3 = Sijantung cultivars.The results showed that the treatment of IAA concentration had no significant effect on allthe variables observed were: percentage of live plants, number of lateral shoots, number of leaves and height of interconnected plantsdurian shoots of Kalimantan cultivars, Kani and Sijantung. Treatment of types of cultivars significantly affected the percentagelive plants, number of lateral shoots, number of leaves and plant height. Durian Ki (Kalimantan) cultivars providethe percentage of larger living plants, the number of lateral shoots and the number of more leaves and plantshigher than K2 (Kani) and Ki (Kalimantan) cultivars. Interaction between concentration treatmentsIAA and type of cultivar have no significant effect on all observed variables, namely: percentage of plantslife, number of lateral shoots, number of leaves and height of top-down durian plants.